Pemanfaatan Wifi Repeater sebagai Solusi Peningkatan Sinyal Wifi bagi Mahasiswa di Lingkungan Kostsehati Kayuwalang dengan Metode Drive Test - Ferdi Ferdiansyah Ferdiansyah; Bambang Irawan; Agus Bahtiar (Universitas Wahid Hasyim, 2024)
Wi-Fi has become the most popular Internet connection among the general public due to its wireless accessibility. However, the limited signal range of Wi-Fi poses challenges. This issue is also prevalent in the environment of Kostsehati Kayuwalang. Specifically, the Wi-Fi signal in the vicinity of room number 6 has been inaccessible within a 50-meter radius, making it difficult for mobile phones and laptops to capture signals, thus causing disruptions when within this area. To address this problem, researchers introduced a signal boosting device, the Wi-Fi Range Extender Pro, to expand the Wi-Fi signal range.The research methodology encompassed Analysis, Design, Implementation, Testing, and Maintenance phases. The findings indicate that the optimization of signal range in Rancaekek Wetan village using the Wi-Fi Range Extender Pro was successful. It has been demonstrated that installing the Wi-Fi extender device allows for coverage in areas previously unreachable by the main Wi-Fi signal, thereby enabling access to the Internet upon installation of the repeater device.However, during speed tests, disparities in received bandwidth were observed. In the main Wi-Fi area, download bandwidth reached 28 Mbit/s depending on the frequency radius, whereas in areas with poor Wi-Fi coverage, download bandwidth was measured at 6.8 Mbit/s, and upload bandwidth at 4.0 Mbit/s. These discrepancies are attributed to bandwidth issues. Therefore, current plans should incorporate bandwidth management implementation and the installation of Wi-Fi repeater devices (Wi-Fi Repeater Extender Pro).